Utilization of STI/HIV services in female sex workers after the health care reform - ศิรประภาศิริ ทวีทรัพย์; จันทร์แย้ม สุรางค์; พึ่งสำราญ ดุสิตา (Disease Control Journal, 2015)
This study is to determine utilization of sexually transmitted infection (STI)/HIV services among female sex workers and associated factors after the health care reform particularly the transfer of STI clinics from the provincial health offices to hospitals. The survey was done in cities of Bangkok, Pattaya, Songkla and ChiangMai. Female sex workers were randomly selected with proportionally stratified to size of types of establishments and freelance. They were approached and asked for participation with verbal consent. Face to face interview with structured questionnaire was done by trained interviewers. Data were analyzed using descriptive and inferential analysis. 813 female sex workers were included for the study. The mean age was 28 years old (range 14-62 years) with 94.7% were Thai. There were 22.5% reported no health insurance, 68.6% were under universal coverage scheme (UHS) and 11.4% were UHS with registration in the working area. The median time working in sex work was 2 years. The median number of clients in the last month was 14. 67.1% of sex workers had ever used STI services while 60.1% used it in the last 12 months. 82.9% had ever got HIV testing and 68.8% did within the last 12 months. Sex workers in karaoke (52.1%), beer bars (54.3%), and freelance (63.3%) had used STI services less than those in ago go bars (80.3%), brothels (81.1%), and massage parlors (94.9%). FSW aged under 20 years was less likely to use STI services (43.1%). Those who entitled to the free health services were more likely to use STI services (79.6%). More efforts should be made to improve services for sex workers not only on STI and HIV but also on reproductive tract problems, alcohol, and drugs with particular focus on those who are younger age; did not entitle to the health benefits in the working area; and worked in context of karaoke, beer bars and freelance.